2011
DOI: 10.4049/jimmunol.1100719
|View full text |Cite
|
Sign up to set email alerts
|

MIP-T3 Is a Negative Regulator of Innate Type I IFN Response

Abstract: TNFR-associated factor (TRAF) 3 is an important adaptor that transmits upstream activation signals to protein kinases that phosphorylate transcription factors to induce the production of type I IFNs, the important effectors in innate antiviral immune response. MIP-T3 interacts specifically with TRAF3, but its function in innate IFN response remains unclear. In this study, we demonstrated a negative regulatory role of MIP-T3 in type I IFN production. Overexpression of MIP-T3 inhibited RIG-I-, MDA5-, VISA-, TBK1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 76 publications
1
47
0
Order By: Relevance
“…TRAF3IP1 is conserved from worms to human and interacts constitutively with TRAF3 through a C-terminal coiled-coil region (Ling and Goeddel, 2000;Guo et al, 2010). A previous study has shown that TRAF3IP1 is a cellular inhibitor of the innate IFN response that impedes TRAF3 complex formation with critical downstream transducers and effectors (Ng et al, 2011), which supports the notion that TRAF3IP1 is biologically important in the regulation of immune responses. Moreover, TRAF3IP1 was also shown to bind microtubules and play an important role in the regulation of cytoskeleton dynamics in cells (Kunitomo and lino, 2007;Guo et al, 2010).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…TRAF3IP1 is conserved from worms to human and interacts constitutively with TRAF3 through a C-terminal coiled-coil region (Ling and Goeddel, 2000;Guo et al, 2010). A previous study has shown that TRAF3IP1 is a cellular inhibitor of the innate IFN response that impedes TRAF3 complex formation with critical downstream transducers and effectors (Ng et al, 2011), which supports the notion that TRAF3IP1 is biologically important in the regulation of immune responses. Moreover, TRAF3IP1 was also shown to bind microtubules and play an important role in the regulation of cytoskeleton dynamics in cells (Kunitomo and lino, 2007;Guo et al, 2010).…”
Section: Introductionsupporting
confidence: 58%
“…A previous study has shown that TRAF3IP1 interacts specifically with TRAF3 and prevents it from forming protein complexes with downstream transducer and effector proteins (Ng et al, 2011). Here, transcription levels of several TRAFs measured in different bivalve species with different bacterial challenges, and resulting from bibliographic analysis, are summarized in Table 2.…”
Section: Pytraf3ip1 Expression Was Ubiquitously Detected Inmentioning
confidence: 99%
“…Collectively, our findings define GnT interactions that inhibit IFN-␤ transcriptional induction by regulating the activation of IRF3/NF-B transcription factors. However, numerous potential effectors that impact TBK1-IRF3 signaling responses (36,40,62,74) require further investigation to define regulatory interactions targeted by discrete hantavirus GnTs.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven of the 32 genes score as high-confidence positives and therefore open new avenues for experiments. For example, TRAF3IP1 is involved in primary cilium formation (Berbari et al ., 2011) and has also been implicated in signal transduction pathways (Niu et al ., 2003; Ng et al ., 2011) but not in chromosome condensation. Our study also clarifies several leads from the literature that had not been followed up.…”
Section: Discussionmentioning
confidence: 99%